2022
DOI: 10.1084/jem.20212491
|View full text |Cite
|
Sign up to set email alerts
|

FNIP1 regulates adipocyte browning and systemic glucose homeostasis in mice by shaping intracellular calcium dynamics

Abstract: Metabolically beneficial beige adipocytes offer tremendous potential to combat metabolic diseases. The folliculin interacting protein 1 (FNIP1) is implicated in controlling cellular metabolism via AMPK and mTORC1. However, whether and how FNIP1 regulates adipocyte browning is unclear. Here, we demonstrate that FNIP1 plays a critical role in controlling adipocyte browning and systemic glucose homeostasis. Adipocyte-specific ablation of FNIP1 promotes a broad thermogenic remodeling of adipocytes, including incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Specifically, FNIP1 was shown to regulate intracellular Ca 2+ levels through stabilization of sarcoendoplasmic reticulum calcium transport ATPase (SERCA) and increasing SERCA Ca 2+ pump activity. This study also suggested a pivotal role for FNIP1 in regulating metabolism and glucose homeostasis in adipocytes, independent of AMPK/mTOR [ 35 ].…”
Section: Fnip1 and Fnip2mentioning
confidence: 90%
See 1 more Smart Citation
“…Specifically, FNIP1 was shown to regulate intracellular Ca 2+ levels through stabilization of sarcoendoplasmic reticulum calcium transport ATPase (SERCA) and increasing SERCA Ca 2+ pump activity. This study also suggested a pivotal role for FNIP1 in regulating metabolism and glucose homeostasis in adipocytes, independent of AMPK/mTOR [ 35 ].…”
Section: Fnip1 and Fnip2mentioning
confidence: 90%
“…These data provide a mechanism that explains the FNIP1-dependent regulation of AMPK in skeletal muscle. FNIP1 regulation of AMPK may be cell-type dependent however, as recent work has demonstrated that FNIP1 regulates cellular respiration in adipocytes in an AMPK/mTOR independent manner [35]. Specifically, FNIP1 was shown to regulate intracellular Ca 2+ levels through stabilization of sarcoendoplasmic reticulum calcium transport ATPase (SERCA) and increasing SERCA Ca 2+ pump activity.…”
Section: Fnip1 Function In Skeletal Muscle and Adipocytesmentioning
confidence: 99%
“…In summary, our recent work suggests that FNIP1 acts as a negative regulator of beige adipocyte thermogenesis to control systemic glucose homeostasis through modulating SERCA ( Yin et al, 2022 ). Linking intracellular Ca 2+ dynamics to adipocyte beiging is of interest, given that it could be an appealing strategy for the treatment of metabolic disorders.…”
mentioning
confidence: 92%
“…In our recent work ( Yin et al, 2022 ), we discovered a previously unrecognized WAT beiging mechanism that targets the folliculin (FLCN) interacting protein 1 (FNIP1)–sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA)–intracellular Ca 2+ axis in adipocytes ( Figure 1 ; commented in Bunk and Kazak, 2022 ). Using multiple Ca 2+ imaging approaches, together with gain- and loss-of-function strategies, we provided clear data demonstrating that FNIP1 is a crucial regulator of intracellular Ca 2+ dynamics and negatively regulates WAT beiging.…”
mentioning
confidence: 99%
“…Calcium (Ca 2 + ) influx into thermogenic adipocytes is regulated by extrinsic adrenergic control ( Chen et al, 2017 ), but a deep mechanistic understanding for how Ca 2+ signaling regulates adaptive thermogenesis is far from complete. Yin et al (2022) identify one piece of the adaptive thermogenesis puzzle by providing evidence that folliculin interacting protein 1 (FNIP1) negatively regulates the browning of white fat by dampening cytosolic Ca 2+ levels. The sarcoendoplasmic reticulum calcium transport ATPase (SERCA) pump is the regulator of Ca 2+ uptake from the cytosol to the ER.…”
mentioning
confidence: 99%